Distributing Knowledge Creation to Include Underrepresented Populations - Heller, Richard F.; Leeder, Stephen R. (International Review of Research in Open and Distributed Learning, 2025)
This paper documents biases in the creation of knowledge through underrepresentation of diverse populations and population groups in the way research is conducted and published, and subsequently, in the way educational resources are developed and delivered. Research that incorporates the experience of distributed population groups will have greater local applicability, and knowledge published and disseminated in ways that make it available to distributed populations will increase likelihood that the research findings will be incorporated into policy and action across the population. The incorporation of knowledge gained from distributed population groups into the educational experience will enrich it and, like the knowledge, make it more relevant to the whole population. We explore the potential for distributing knowledge creation to contribute in these ways and what changes are required in the way that higher education is organised to maximise distributed knowledge creation, including collaborative co-creation of knowledge and a collaborative capacity-building programme to ensure its sustainability. We propose that the principles described for a distributed university, where education is disseminated largely online through regional hubs to correct local and global inequalities in access, would be suitable to support the development of structures for distributing knowledge creation. Appropriate governance structures should be developed, of which co-creation of knowledge would be an essential component.